Pengembangan Sistem Pendingin Cold Box Penyimpanan Ikan Dengan Pemanfaatan Pcm - Silviana Simbolon; Sigit Bagus Hakim; Marwan Marwan; Sukendar Sukendar; Yuliarman Yuliarman; Kusdi prijono; Muhammad Yunus (Politeknik Negeri Padang, 2023)
One of the technologies in the refrigeration system to improve power and cost efficiency is to utilize technology to overcome this problem is to use phase change materials (PCM) to replace standard refrigerants. The purpose of this study is an attempt to reduce the operational cost of fish storage with a cold box cooling system for fish storage by utilizing PCM. The method used in this research is the experimental method. From the results of the study obtained data using a variation of 2 PCM compressor takes 219.7 minutes when mode ON for 7 hours of testing, variation 4 PCM compressor takes 202.7 minutes when mode ON for 7 hours of testing, variation 6 PCM takes 177.4 minutes when mode ON for 7 hours of testing. With this variation 6 PCMs are more optimal in helping to reduce compressor working time. The more the number of PCMs placed in the cold box can help reduce the compressor on/off cycle and the electrical energy required by the compressor is more efficient, the most efficient variation is the 6 PCM variation with a power efficiency of 15.31%. With the use of PCM can save operational costs up to 59.54% compared to using ice blocks. The design of cold boxes using PCM will benefit after 3 months of use compared to using block ice.